Local dynamics of proteins and DNA evaluated from crystallographic B factors - Schneider, Bohdan; Gelly, Jean Christophe; de Brevern, Alexandre G; Černý, Jiří (Acta crystallographica. Section D, Biological crystallography, 2014)
The dynamics of protein and nucleic acid structures is as important as their average static picture. The local molecular dynamics concealed in diffraction images is expressed as so-called B factors. To find out how the crystal-derived B factors represent the dynamic behaviour of atoms and residues of proteins and DNA in their complexes, the distributions of scaled B factors from a carefully curated data set of over 700 protein-DNA crystal structures were analyzed [Schneider et al. (2014), Nucleic Acids Res. 42, 3381-3394]. Amino acids and nucleotides were categorized based on their molecular neighbourhood as solvent-accessible, solvent-inaccessible (i.e. forming the protein core) or lying at protein-protein or protein-DNA interfaces; the backbone and side-chain atoms were analyzed separately. The B factors of two types of crystal-ordered water molecules were also analyzed. The analysis confirmed several expected features of protein and DNA dynamics, but also revealed surprising facts. Solvent-accessible amino acids have B factors that are larger than those of residues at the biomolecular interfaces, and core-forming amino acids are the most restricted in their movement. A unique feature of the latter group is that their side-chain and backbone atoms are restricted in their movement to the same extent; in all other amino-acid groups the side chains are more floppy than the backbone. The low values of the B factors of water molecules bridging proteins with DNA and the very large fluctuations of DNA phosphates are surprising. The features discriminating different types of residues are less pronounced in structures with lower crystallographic resolution. Some of the observed trends are likely to be the consequence of improper refinement protocols that may need to be rectified.
Keywords: Proteins; proteiny; DNA; Crystallography, X-Ray; krystalografie rentgenová